FDTD Simulation of Magnetic Field Distribution in Normal and Blood Cancer for Treatment. Issue 1 (June 2021) - Zulfa, V Z; Farahdina, U; Firdhaus, M; Aziz, I; Nasori, N; Endarko, E; Darsono, D; Rubiyanto, A
Abstract: Non-invasive cancer treatment has the potential to eliminate infection and scar formation associated with surgery to minimize side effects. Light stimulation can use for treatment to increase efficiency, reduce treatment costs, eliminate infection, etc. Magnetic fields can improve blood circulation in tissues and stimulate the body's metabolism. The magnetic field can induce joule heating and expand the blood vessels of cancerous tumors. These blood vessels increase the possibility of excess oxygen to enter the tumor creating obstacles to the survival of oxygen-rich cancers. In this study, we investigate finite difference times domain (FTDT) simulation of magnetic field in normal and blood cancer. The low frequency with range 10-10 6 is used in this study. The maximum magnetic field for normal blood and CLL1 is 400 nm and 250 nm in 125 cm electrode size. While for 50 nm electrode size, the maximum magnetic field in normal blood and CLL 1 is 400 nm and 300 nm. But there The maximum magnetic field for normal blood and CLL1 is 400 nm and 250 nm in 125 cm electrode size. While for 50 nm electrode size, the maximum magnetic field in normal blood and CLL 1 is 400 nm and 300 nm. But there is no peak for blood cancer in final stage CLL2.